Research Advances on the Interactions between Rabies Virus Structural Proteins and Host Target Cells: Accrued Knowledge from the Application of Reverse Genetics Systems - Juanbin Yin; Xiangwei Wang; Ruoqing Mao; Zhixiong Zhang; Xin Gao; Yingying Luo; Yuefeng Sun; Xiangping Yin (Viruses, 2021)
Rabies is a lethal zoonotic disease caused by lyssaviruses, such as rabies virus (RABV), that results in nearly 100% mortality once clinical symptoms appear. There are no curable drugs available yet. RABV contains five structural proteins that play an important role in viral replication, transcription, infection, and immune escape mechanisms. In the past decade, progress has been made in research on the pathogenicity of RABV, which plays an important role in the creation of new recombinant RABV vaccines by reverse genetic manipulation. Here, we review the latest advances on the interaction between RABV proteins in the infected host and the applied development of rabies vaccines by using a fully operational RABV reverse genetics system. This article provides a background for more in-depth research on the pathogenic mechanism of RABV and the development of therapeutic drugs and new biologics.